The Problem of Identity and Eternal Objects in Whitehead - Schulz, Dwayne (Process studies, 2017)
This article is an exploration of the problem of identity in Whitehead. Both the Platonic and the nominalistic tendencies in Whitehead are analyzed. His theory of eternal objects is criticized and a process view of identity based on tropes is defended.